2020
DOI: 10.1097/bot.0000000000001780
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tibial and Femoral Bone Defects With Bone Transport Over an Intramedullary Nail

Abstract: To evaluate the results of the bone transport over an intramedullary nail (BTON) technique for the treatment of segmental bone defects.Design: Retrospective review of case series. Setting: Level 1 trauma center. Patients/Participants: We included 40 patients who underwent reconstruction of the lower limb with BTON technique between 2000 and 2018. The technique was performed in the tibial segments in 21 patients and in the femoral segments in 19 patients. Intervention: The surgical technique was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…A subgroup of six studies 45 , 46 , 50 , 51 , 53 , 54 , 57 focusing on the bone transport approach showed a primary union rate of 89.7% with a mean external fixator time of 6.6 months (range 4.2–9.3 months), a complication rate of 66.9%, a reintervention rate of 29.8% and a failure rate of 3.7%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A subgroup of six studies 45 , 46 , 50 , 51 , 53 , 54 , 57 focusing on the bone transport approach showed a primary union rate of 89.7% with a mean external fixator time of 6.6 months (range 4.2–9.3 months), a complication rate of 66.9%, a reintervention rate of 29.8% and a failure rate of 3.7%.…”
Section: Resultsmentioning
confidence: 99%
“…The average bone defect was 8.8 cm (range 2.7–28 cm), and the average follow-up was 35.7 months (range 6–168 months). The Ilizarov method with external fixation was used in 15 studies 35 , 36 , 46 50 , 52 , 56 , 59 62 , 65 , intramedullary nailing and/or external fixation was used in eight studies 43 , 45 , 51 , 53 55 , 57 , 64 , a monolateral external fixation was used in one study 44 , and bone transport with a five-ring circular external fixator in one study 58 . One of the studies in the Ilizarov group was a case–control comparing bifocal versus trifocal fibular transfer, showing better primary union rate, fewer complications and reinterventions in the trifocal group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment methods for such patients are complicated; the results are not ideal; and the incidence of disability is high. During surgery, large pieces of sequestrum need to be removed, and local bone defects will also occur during the removal, which has a certain impact on the postoperative recovery of patients [ 1 ]. At present, for such patients, autologous iliac bone transplantation is mostly used.…”
Section: Introductionmentioning
confidence: 99%
“…Bas et al included 40 patients who experienced the lower limb reconstruction by hybrid transport technique from 2000 to 2018 and the total incidence of complications was 57.5%. They found that the hybrid transport technique was related to low cost due to the short treatment cycle, low complication incidence, and rapid rehabilitation [ 29 ]. Oh et al included 12 patients using the hybrid transport technique and 3 of them suffered from postoperative complications [ 26 ].…”
Section: Discussionmentioning
confidence: 99%